The Use of Footstep Sounds as Rhythmic Auditory Stimulation for Gait Rehabilitation in Parkinson’s Disease: A Randomized Controlled Trial - Murgia, Mauro; Pili, Roberta; Corona, Federica; Sors, Fabrizio; Agostini, Tiziano A.; Bernardis, Paolo; Casula, Carlo; Cossu, Giovanni; Guicciardi, Marco; Pau, Massimiliano (Frontiers in Neurology, 2018)
Background. The use of rhythmic auditory stimulation (RAS) has been proven useful in the management of gait disturbances associated with Parkinson’s disease (PD). Typically, the RAS consists of metronome or music-based sounds (artificial RAS), while ecological footstep sounds (ecological RAS) have never been used for rehabilitation programmes. Objective. The aim of the present study was to compare the effects of a rehabilitation programme integrated either with ecological or with artificial RAS. Methods. An observer-blind, randomized controlled trial was conducted to investigate the effects of 5 weeks of supervised rehabilitation integrated with RAS. Thirty-eight individuals affected by PD were randomly assigned to one of the two conditions (ecological vs. artificial RAS); thirty-two of them (age 68.2 ± 10.5, Hoehn and Yahr 1,5–3) concluded all phases of the study. Spatio-temporal parameters of gait and clinical variables were assessed before the rehabilitation period, at its end, and after a 3-month follow-up. Results. Thirty-two participants were analyzed. The results revealed that both groups improved in the majority of biomechanical and clinical measures, independently of the type of sound. Moreover, exploratory analyses for separate groups were conducted, revealing improvements on spatio-temporal parameters only in the ecological RAS group. Conclusions. Overall, our results suggest that ecological RAS is equally effective compared to artificial RAS. Future studies should further investigate the role of ecological RAS, on the basis of information revealed by our exploratory analyses. Theoretical, methodological and practical issues concerning the implementation of ecological sounds in the rehabilitation of PD patients are discussed. Trial Registration. ClinicalTrials.gov, NCT03228888